Apoflavodoxin (un)folding followed at the residue level by NMR. - van Mierlo, C. P. (Cold Spring Harbor Laboratory Press, 2000)
The denaturant-induced (un)folding of apoflavodoxin from Azotobacter vinelandii has been followed at the residue level by NMR spectroscopy. NH groups of 21 residues of the protein could be followed in a series of 1H-15N heteronuclear single-quantum coherence spectra recorded at increasing concentrations of guanidinium hydrochloride despite the formation of protein aggregate. These NH groups are distributed throughout the whole apoflavodoxin structure. The midpoints of unfolding determined by NMR coincide with the one obtained by fluorescence emission spectroscopy. Both techniques give rise to unfolding curves with transition zones at significantly lower denaturant concentrations than the one obtained by circular dichroism spectroscopy. The NMR (un)folding data support a mechanism for apoflavodoxin folding in which a relatively stable intermediate is involved. Native apoflavodoxin is shown to cooperatively unfold to a molten globule-like state with extremely broadened NMR resonances. This initial unfolding step is slow on the NMR chemical shift timescale. The subsequent unfolding of the molten globule is faster on the NMR chemical shift timescale and the limited appearance of 1H-15N HSQC cross peaks of unfolded apoflavodoxin in the denaturant range studied indicates that it is noncooperative.